Perceptions of important outcomes of moral case deliberations: a qualitative study among healthcare professionals in childhood cancer care - Weiner, Charlotte (BMC Med Ethics, 2021)
BACKGROUND: In childhood cancer care, healthcare professionals must deal with several difficult moral situations in clinical practice. Previous studies show that morally difficult challenges are related to decisions on treatment limitations, infringing on the child's integrity and growing autonomy, and interprofessional conflicts. Research also shows that healthcare professionals have expressed a need for clinical ethics support to help them deal with morally difficult situations. Moral case deliberations (MCDs) are one example of ethics support. The aim of this study was to describe the MCD-related outcomes that healthcare professionals in childhood cancer care considered important, before MCDs were implemented, in order to facilitate the implementation of MCDs in childhood cancer care in Sweden. METHODS: This study is based on qualitative data. Healthcare professionals, mostly representing registered nurses, nursing assistants and physicians, working at childhood cancer care centres in Sweden, were invited to respond to the translated and content validated European MCD Outcomes Instrument, before participating in regular MCDs. Answers to the main open-ended question, included in the questionnaire, was analysed according to systematic text condensation. RESULTS: Data was collected from 161 responses from the healthcare professionals. The responses included healthcare professionals’ perceptions of which MCD-related outcomes they found important for handling moral challenges. Three different themes of important outcomes from the analysis of the data are presented as follows: Interprofessional well-being in team interactions on a team level; Professional comfort when dealing with moral challenges on a personal level; and Improved quality of care for the child and the family on a care level. CONCLUSIONS: Healthcare professionals in childhood cancer care considered it important that ethics support could enhance the well-being of interprofessional teams, support healthcare professionals on an individual level and improve quality of care. The results of this study can be used in current and future training for MCD-facilitators. When knowing the context specific important MCD-outcomes, the sessions could be adapted. Managers in childhood cancer care would benefit from knowing about the specific important outcomes for their target group because they could then create relevant working conditions for clinical ethics support.